PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE LEARNING TOURNAMENT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI SMPN 2 RANAH PESISIR - Mai Darwin, Witri; Aima, Zulfitri; Mardiyah, Ainil (STKIP PGRI Sumbar, 2014)
Â ABSTRACTÂ The background of this researchÂ is students are still low to understandÂ the concept of mathematic and they donât want to ask some question, share opinion about the materialÂ that have been not understood yet. To solve the problem, teacher should apply active learning like learning tournament strategy. The purpose of this research is to know the students in understanding mathematic concept by applying learning tournament is better than convensional learning strategy. Kinds of this is experimentÂ research. The population in this research is grade nineth SMPN 2 RanahÂ Pesisir. Instrument that used in this research used essay from reliability 0,93. The technique of data analysis usedÂ T-test one side. Based on the result of hypothesis obtained T-table = 1,6735 T-count = 3,86 so Tcount > Ttable. There for hypothesis is reviced at level confidence 95%. In conclusion students mathematic concept by applying learning tournament strategy is better than convensional learning strategy in class grade nineth SMPN 2 Ranah Pesisir.Â